Libraries as publishers: a winning combination. Issue 2 (11th May 2015) - Simser, Charlene N.; Stockham, Marcia G.; Turtle, Elizabeth
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to present a case study of the Kansas State University Libraries open access publishing endeavor, New Prairie Press (NPP). The library as publisher is a growing worldwide movement. Many academic and research libraries see it as their strategic mission to highlight and disseminate the research and creative work being done by faculty and students at their institutions. Topics covered include current activities, business plan development, needed technology and skill sets and migration from an open source platform to a hosted solution. Design/methodology/approach – The article presents a case study of one library's experience of establishing a publishing press – libraries as publishers. Findings – This article finds that during the years of operation, NPP staff members have learned much about the role that libraries can play in the evolving scholarly communications landscape. Originality/value – This article finds that the continual assessment of value, alignment with strategic goals and funding will be critical to ensure future growth and direction of the press.